Comparative Analysis of Molecular Diagnostic Techniques for Pulmonary Tuberculosis: A Literature Review - Rachmatunisa, Anita; Oktariana, Desi (Biomedical Journal of Indonesia, 2025)
Pulmonary tuberculosis is a global health problem that requires early and precise diagnosis for effective control. In this literature review, we compare several molecular diagnostic techniques used in the detection of pulmonary tuberculosis, such as Polymerase Chain Reaction (PCR), Whole Genome Sequencing (WGS), and Next Generation Sequencing (NGS), as well as Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)-based Diagnostic Techniques. Polymerase Chain Reaction stands out for its high sensitivity, although time-consuming and high operational costs. Meanwhile, whole genome sequencing and next generation sequencing have detailed tuberculosis (TB) strain identification capabilities but have high costs and limited availability. On the other hand, CRISPR-based diagnostic techniques offer speed and low cost but are still in the advanced stages of development. Challenges in implementing new techniques include technical barriers, logistics, and improving sensitivity and specificity. Suggestions for future research include the development of more effective, faster, and affordable techniques, especially in developing portable diagnostic tests for accessibility of pulmonary tuberculosis diagnosis in various regions.